Revitalizing Etu Traditional Boxing as Local Wisdom for Sustainable Tourism Policy Development: A Case Study of Wuliwalo Village, Nagekeo Regency, Indonesia - Yohana Fransiska Medho; Maximianus Ardon Bidi; Droste Go Jewa (Journal Public Policy, 2026)
The Etu traditional boxing tradition is a form of local wisdom of the Wulu people of Wuliwalo Village, Nagekeo Regency, NTT. It symbolizes courage, social solidarity, and customary conflict resolution. However, this tradition faces challenges due to modernization and declining interest from the younger generation. The aim of this study is to identify local values contained in Etu, analyze the revitalization strategies carried out by the community, and evaluate the role of Etu in the development of cultural tourism. The method used was descriptive qualitative with a case study approach. Data collection techniques included in-depth interviews, participant observation, and documentation. The research location was in Wulu, Wuliwalo Village, Mauponggo District, Nagekeo Regency. The research results show that Etu still holds strong cultural significance, embodied in the values of restrained courage, restorative solidarity, and discipline that respects tradition. Revitalization efforts have been carried out through youth involvement, systematic documentation, scheduling Etu in the village's annual cultural calendar (as an educational demonstration), and collaboration with tourism awareness groups (Pokdarwis). This revitalization has resulted in increased youth participation, the emergence of local economic opportunities, and the strengthening of cultural identity. In conclusion, if managed in a participatory and sustainable manner, Etu has great potential to become a unique and authentic community-based tourist attraction, providing significant social and economic benefits, and strengthening local cultural identity.